Controlling the carbon-bio interface: ex-situ and in-situ studies of fundamental biomolecule--carbon reactions - ZEN, FEDERICO (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2017)
Carbon materials and nanomaterials are of great interest for biological applications such as implantable apparatus and nanoparticle vectors. In particular, amorphous carbon is extensively used as coating for biomedical devices because of a combination of desirable physical/chemical properties that underpin their good performances. However, an explanation of the biocompatibility of carbon-coated devices has not yet been found. Importance in the interaction of biomaterials with biological fluids and tissues has been credited to the events taking place during the initial stages of surface conditioning. Proteins and lipids are examples of biomolecules first adsorbing at the surface after implantation. Therefore, to realize the potential of carbon biomaterials it is critical to control formation and composition of the protein corona in biological media. In this thesis an investigation into the protein interfacial interactions at different amorphous carbon surfaces is reported. A detailed adsorption study of albumin, lysozyme and fibrinogen was carried out at carbon surfaces functionalized with aryldiazonium layers bearing mono- and di-saccharide glycosides. Ex-situ results show that that glycan layers prevent unspecific protein adsorption, in particular in the case of the tested di-saccharide. Antifouling properties at phenylglycoside layers correlate positively with wetting behaviour and Lewis basicity. The dynamic of protein adsorption were studied using a combination of in-situ techniques: nanoplasmonic sensing were demonstrated to be optimal for the comparative investigation of protein interactions at carbon surfaces with dissimilar dielectric properties; results obtained by quartz crystal microbalance measurements suggested that protein conformation at carbohydrate layers likely differs from that at bare carbon.
Controlling the Carbon-Bio Interface: ex-situ and in-situ Studies of Fundamental Biomolecule-Carbon Interactions
APPROVED
Keywords: amorphous carbon; protein adsorption; antifouling; quartz crystal microbalance; localized surface plasmon resonance; biomaterial